Collision-Induced C_{60} Rovibrational Relaxation Probed by State-Resolved Nonlinear Spectroscopy - Lee R. Liu; P. Bryan Changala; Marissa L. Weichman; Qizhong Liang; Jutta Toscano; Jacek Kłos; Svetlana Kotochigova; David J. Nesbitt; Jun Ye (PRX Quantum, 2022)
Quantum state-resolved spectroscopy was recently achieved for C_{60} molecules when cooled by buffer gas collisions and probed with a midinfrared frequency comb. This rovibrational quantum state resolution for the largest molecule on record is facilitated by the remarkable symmetry and rigidity of C_{60}, which also present new opportunities and challenges to explore energy transfer between quantum states in this many-atom system. Here we combine state-specific optical pumping, buffer gas collisions, and ultrasensitive intracavity nonlinear spectroscopy to initiate and probe the rotation-vibration energy transfer and relaxation. This approach provides the first detailed characterization of C_{60} collisional energy transfer for a variety of collision partners, and determines the rotational and vibrational inelastic collision cross sections. These results compare well with our theoretical modeling of the collisions, and establish a route towards quantum state control of a new class of unprecedentedly large molecules.